Islamic Calligraphy Art Training to Increase the Creativity of Al-Falah MDTA Students in Telarsari Village - Sa'adah, Nur Sa'adah; Nurfitriyah, Shalihat; Ahmadiah, Didih (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
MDTA Al-Falah is an Islamic madrasah located in Hamlet 2 Cibango Rt.03/Rw.06 Telarsari Village, Jatisari District, Karawang Regency. Learning at MDTA Al-Falah is carried out every day, from Monday to Saturday at 14.00 - 16.00 in the afternoon. The students at MDTAl-Falah still lack skills in the art of Islamic calligraphy, because basically at MDTA Al-Falah itself there is no training in the art of Islamic calligraphy specifically for the students. Based on the problems at MDTA Al-Falah, the author decided to carry out Islamic calligraphy art training activities to increase the creativity of MDTA Al-Falah students. The KPM approach used in research is the PAR method or Participatory Action Research. The training program itself was carried out at MDTA Al-Falah involving MDTA Al-Falah students as the main assets in this program. Training activities were carried out in four meetings in stages. Based on the training process and the calligraphy results of the students, it can be concluded that holding Islamic calligraphy art training activities can increase the creativity of MDTA Al-Falah students.